1986
DOI: 10.1017/s0022112086001714
|View full text |Cite
|
Sign up to set email alerts
|

Organized structures in a turbulent plane jet: topology and contribution to momentum and heat transport

Abstract: In the self-preserving region of a slightly heated turbulent plane jet, conventional isocorrelation contours of velocity and temperature fluctuations support the existence of organized large-scale structures. Temperature fronts associated with these structures were visually detected using a spanwise rake of cold wires. This method of detection was then used to condition velocity and temperature fluctuations and products of these fluctuations. Ensemble-averaged velocity vectors, constructed in the plane of main… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
43
1
1

Year Published

1989
1989
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(48 citation statements)
references
References 16 publications
3
43
1
1
Order By: Relevance
“…Although the turbulence intensity could intuitively be associated with the flow mixing, it has been demonstrated that the Reynolds shear stresses uv, uw, and vw are responsible of the flow kinetic energy transport (Antonia et al, 1986;Cal et al, 2010;Cantwell and Coles, 1983;Escudie and Line, 2003;Hussain, 1983;and Reynolds and Hussain, 1972) and that as such they must be taken into consideration for evaluating the turbulent mixing in a particular region of the flow. For this reason, the last term of Equation (2), which represents the spatial gradients of the flux of mean-flow kinetic energy, has been evaluated in the x-y plane as U ¼ Àuðu 0 v 0 Þ (streamwise mean-flow kinetic energy flux in the radial direction).…”
Section: F Wake Mixingmentioning
confidence: 99%
“…Although the turbulence intensity could intuitively be associated with the flow mixing, it has been demonstrated that the Reynolds shear stresses uv, uw, and vw are responsible of the flow kinetic energy transport (Antonia et al, 1986;Cal et al, 2010;Cantwell and Coles, 1983;Escudie and Line, 2003;Hussain, 1983;and Reynolds and Hussain, 1972) and that as such they must be taken into consideration for evaluating the turbulent mixing in a particular region of the flow. For this reason, the last term of Equation (2), which represents the spatial gradients of the flux of mean-flow kinetic energy, has been evaluated in the x-y plane as U ¼ Àuðu 0 v 0 Þ (streamwise mean-flow kinetic energy flux in the radial direction).…”
Section: F Wake Mixingmentioning
confidence: 99%
“…Experimental studies in the past 40 years acquired abundant evidence and data supporting the dynamical role of CS. CS control entrainment and mixing of species (Dimotakis & Brown 1976, Dutton & Lucht 2006, and contribute comparable amount to the Reynolds stresses and heat flux as does random turbulence (Hussain & Zaman 1985, Antonia et al 1986). The Reynolds stresses may take negative values in the region of positive mean-flow gradient, indicating that closure models of the mean-flow gradient type are inappropriate.…”
Section: Introductionmentioning
confidence: 99%
“…Of course upstream events doubtless play a role: indeed Didden & Ho (1985) show that the ring vortices periodically generated in the shear layer of an axisymmetric impinging jet induce unsteady separation in the impingment region, a feature further explored by Fox et al (1993). But the evolution of coherent structures in a plane jet (Antonia et al 1986), not to mention plane impinging jet, are not nearly so well documented as say those in an axisymmetric impinging jet or in a plane mixing layer. The object of the present work therefore was to determine not only the phase evolution of the three-dimensional vorticity field in the impingment region, but also the structure of the plane jet.…”
Section: Introductionmentioning
confidence: 99%